Critique of Forough Farrokhzad's “Let’s Believe in the Beginning of the Cold Season” with the Interpretive Semiotic Approach of Umberto Eco - Shirzad Tayefi; Niloofar Bakhtiari (مطالعات زبانی و بلاغی)
Hermeneutic semiotics is a platform that can be used to trace dynamic meanings in open texts. This approach provides the possibility of comprehensive investigation and creation of infinite impressions to form a dialectic between the text and the reader. What Umberto Eco expresses by combining Louis Hjelmslev’s ideas about the relationship between expression and content with American pragmatism, leads to encyclopedic semantic criteria, which is proposed as the equivalent of a dictionary of semantics. In the Eco’s semiotics system, all the components of the text, such as metonymy, metaphor, symbol, figures of speech, musicality, etc., are examined in an all-round textual and contextual interpretation and are measured using the axes derived from the four Aristotelian causes to provide a scientific and standard interpretation, from the point of view of the reader of the model. In the current research, Forough Farrokhzad’s poem “Let’s Believe in the Beginning of the Cold Season” (“Imān Biāvarim Be Āqhāze Fasle Sard”) has been examined as an interpretable, symbolic, myth-oriented text in its cultural, ideological, semantic, aesthetic context. The decoding of recurring signs of the poem has been explained with the help of an encyclopedic method at different levels of meaning.